Skin lesion assessment and management model: optimising existing resources in the management of non-melanoma skin cancer - Caitlin O’Hare; Michael McKeough; Melanie Hickson; Rebekah Ferris; Jay Wiper; Michael Wagels (Australasian Journal of Plastic Surgery)
**Background:** Skin cancer is a relatively common cancer in Australia with early diagnosis and simple treatment conferring a high likelihood of cure. The aim of this study was to implement a ‘see-and-treat’ clinic, using pre-existing infrastructure, to investigate whether this model of care would reduce waiting times and costs and give high levels of patient satisfaction.